2021
DOI: 10.57170/jcs.v3i3.17
|View full text |Cite
|
Sign up to set email alerts
|

Penyuluhan Pentingnya Pemberian Asi Ekslusif Dan Manfaatnya Pada Ibu Dan Bayi Di Desa Sopa Kecamatan Kindang Kabupaten Bulukumba

Abstract: Exclusive breastfeeding is breastfeeding during the .first 6 months of a baby's life without food or other drinks except vitamins, drugs and ORS. Breast milk functions as an antibody, fulfilling the nutritional intake of the baby and reduces the rate of morbidity and infant mortality. Breast milk is the best food for the baby when he/she was born. Many researches prove that breast milk is the best and primary food for the baby because in the breast milk contain an antibody that the baby need to resist any kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…This effort is carried out in 3 stages, namely during pregnancy (antenatal), when the mother is in labor until she leaves the hospital (perinatal), and during the next breastfeeding period until the child is 2 years old (postnatal). In line with that, Khotimah's research also reminded the importance of counseling (Khatimah, Akhfar, & Khaera, 2021). This community service activity adds knowledge and solutions for pregnant women who are preparing for the lactation process and can maximize exclusive breastfeeding.…”
Section: Figure 1 Extension Activities C Activity Evaluationmentioning
confidence: 78%
“…This effort is carried out in 3 stages, namely during pregnancy (antenatal), when the mother is in labor until she leaves the hospital (perinatal), and during the next breastfeeding period until the child is 2 years old (postnatal). In line with that, Khotimah's research also reminded the importance of counseling (Khatimah, Akhfar, & Khaera, 2021). This community service activity adds knowledge and solutions for pregnant women who are preparing for the lactation process and can maximize exclusive breastfeeding.…”
Section: Figure 1 Extension Activities C Activity Evaluationmentioning
confidence: 78%
“…Based on the results of monitoring and evaluation, it was found that there was an increase in the application of EPDS by midwives for early detection postpartum maternal psychological problems, namely from 66.7 to 88.9. It is recommended that midwives increase efforts to detect early postpartum depression in every postpartum mother by using EPDS both during home visits and when clients visit service facilities (Khatimah, Akhfar, & Khaera, 2021). There are several ways to prevent postpartum depression.…”
Section: Introductionmentioning
confidence: 99%